2009
DOI: 10.1053/j.gastro.2009.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Liver Sinusoidal Endothelial Cell Lectin, LSECtin, Negatively Regulates Hepatic T-Cell Immune Response

Abstract: Our results reveal that LSECtin is a novel regulator of T cells and expose a crucial mechanism for hepatic T-cell immune suppression, perhaps opening up a new approach for treatment of inflammatory diseases in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 29 publications
2
90
0
2
Order By: Relevance
“…We previously reported that LSECtin inhibited T cell immune responses, including decreased T cell activation and proliferation and the downregulation of T cell-derived cytokines (10,21). Therefore, to understand the mechanism by which LSECtin suppresses the intrahepatic effector functions of CD8 + T cells in a mouse model of adenovirus infection, we compared the T cell proliferation in the liver through in vivo BrdU labeling.…”
Section: /2 Mice Upon Viral Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that LSECtin inhibited T cell immune responses, including decreased T cell activation and proliferation and the downregulation of T cell-derived cytokines (10,21). Therefore, to understand the mechanism by which LSECtin suppresses the intrahepatic effector functions of CD8 + T cells in a mouse model of adenovirus infection, we compared the T cell proliferation in the liver through in vivo BrdU labeling.…”
Section: /2 Mice Upon Viral Infectionmentioning
confidence: 99%
“…Screening of effective small interfering RNA for silencing mouse LSECtin expression in the liver was described previously (10). mLSECtinshort hairpin RNA (shRNA) were cloned into the pSIREN-DNR-DsRed vector (Clontech).…”
Section: Plasmids For Hydrodynamic Injectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Tim-3/galectin-9 (Gal-9) pathway modulation affects tumor growth (25); LSECtin, which belongs to the C-type lectin receptor superfamily, is a type II transmembrane protein that is highly expressed in the liver (26). Our previous studies revealed that LSECtin, when expressed in the liver, acted as a co-inhibitory molecule and limited the ability of T-cell immunity to promote HBV tolerance (27,28). Immunologically, tumors are quite similar to chronic viral infections.…”
Section: Introductionmentioning
confidence: 99%